A multidimensional analysis of socioeconomic factors in housing policy in the Eurozone countries (2010–2014) - Santos, António Duarte (2017)
The latest global economic and financial crisis has had adverse social consequences in many areas, including income and the social situation of households and their living conditions, especially when the housing phenomenon is addressed. The reality of this uncertainty has made the study of the housing phenomenon even more relevant, in particular from the perspective of an analysis of its evolution. In this context, we revisit EUROSTAT’s databases. This analysis was done for twelve Euro Area countries over five years, using the HJ-BIPLOT method developed by Galindo (1986). This multidimensional approach identified and represented twelve Eurozone sample countries in latent constructs of reduced dimensionality related to the housing policy problem. The simultaneous factorial representation identified (a) the most relevant variables to characterize these countries, (b) their trajectories during the period in analysis, and (c) the relations between variables, between countries, and between variables and countries. This approach also identified the most significant factors contributing to the countries' performance. This methodological approach can be useful in housing research, when studying data of a multivariate nature, and is also, by its visual interpretation, a potential tool for producing richer information not only for academia but also for policy makers.